2016
DOI: 10.1097/pts.0000000000000196
|View full text |Cite
|
Sign up to set email alerts
|

Medication Administration Errors in a University Hospital

Abstract: Medication administration errors represent a major problem in the hospital that needs urgent intervention to optimize medication administration process. The intervention should consider the identified significant determinants of medication administration errors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
45
1
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(56 citation statements)
references
References 16 publications
5
45
1
3
Order By: Relevance
“…Medication administration errors of this magnitude are likely to result in harming the patient and may erode public confidence in nursing care. Several studies and systematic reviews around the world in different countries reported likewise high magnitude of MAEs [2,3,6,18].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Medication administration errors of this magnitude are likely to result in harming the patient and may erode public confidence in nursing care. Several studies and systematic reviews around the world in different countries reported likewise high magnitude of MAEs [2,3,6,18].…”
Section: Discussionmentioning
confidence: 96%
“…Similarly, the mortality rate attributed to adverse drug events was 0.1% [2]. A direct observational study conducted in Egypt indicated 0.77% of inpatients being harmed by MAEs and needed either extended hospitalization or intervention [18]. Furthermore, in Ethiopia, 1.5% of patients experienced actual adverse drug events associated with medication errors [19].…”
Section: Introductionmentioning
confidence: 99%
“…[13] Medication errors lead to an increase in the duration of hospitalization[14] and disability and death in up to 6.5% of hospital admissions. [15]…”
Section: Introductionmentioning
confidence: 99%
“…A maior taxa de erro foi detectada em injeções, especialmente na via intravenosa (39,58%) e dentre os erros mais frequentes estava a técnica errada (78,90%). (9) Esses dados, além de alarmantes, evidenciam a importância da proposição de práticas seguras e do uso de instrumentos de avaliação capazes de fornecer informações precisas sobre o processo de administração de medicamentos nos EAS. Outrossim, as questões validadas do instrumento final demonstram sua capacidade de utilização em qualquer EAS que utilize "medicamentos para profilaxia, exames diagnósticos, tratamento e medidas paliativas".…”
Section: Introduçâounclassified